PISN-explorer: hunting the descendants of very massive first stars. Issue 1 (20th January 2023) - Aguado, D S; Salvadori, S; Skúladóttir, Á; Caffau, E; Bonifacio, P; Vanni, I; Gelli, V; Koutsouridou, I; Amarsi, A M
ABSTRACT: The very massive first stars ( m > 100 $\rm M_{\odot }$ ) were fundamental to the early phases of reionization, metal enrichment, and supermassive black hole formation. Among them, those with $140\le \rm m/\rm M_{\odot }\le 260$ are predicted to evolve as Pair Instability Supernovae (PISN) leaving a unique chemical signature in their chemical yields. Still, despite long searches, the stellar descendants of PISN remain elusive. Here we propose a new methodology, the PISN-explorer, to identify candidates for stars with a dominant PISN enrichment. The PISN-explorer is based on a combination of physically driven models, and the FERRE code; and applied to data from large spectroscopic surveys (APOGEE, GALAH, GES, MINCE, and the JINA data base). We looked into more than 1.4 million objects and built a catalogue with 166 candidates of PISN descendants. One of which, 2M13593064+3241036, was observed with UVES at VLT and full chemical signature was derived, including the killing elements, Cu and Zn. We find that our proposed methodology is efficient in selecting PISN candidates from both the Milky Way and dwarf satellite galaxies such as Sextans or Draco. Further high-resolution observations are highly required to confirm our best selected candidates, therefore allowing us to probe the existence and properties of the very massive First Stars.